2016
DOI: 10.1002/cbin.10706
|View full text |Cite
|
Sign up to set email alerts
|

TWEAK increases SIRT1 expression and promotes p53 deacetylation affecting human hepatic stellate cell senescence

Abstract: To detect the effects of tumor necrosis factor-like weak inducer of apoptosis (TWEAK) on SIRT1 expression and p53 deacetylation, involving cell senescence, in activated human hepatic stellate cell (HSC) in vitro, human HSC LX-2 was cultured with TWEAK for 24 h. The result showed that the expression of membrane receptor Fn14 was remarkably increased by TWEAK, which upregulated SIRT1 in LX-2 cells, detected by Western blotting and real-time PCR. The expression of p53 was not significantly altered; however, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 34 publications
1
9
0
1
Order By: Relevance
“…Cells were incubated at 37˚C in a humidified atmosphere of 5% CO 2 and 95% air and grown to 70 to 80% confluence. For the experiments, the HUVECs were treated with 50, 100 and 200 ng/ml TWEAK respectively based on previous studies (15)(16)(17). As for Fn14 siRNA, for each well of a 6-well plate, cells were transfected with 5 µl siRNA (20 µM) or negative control (Ncontrol group) using Lipofectamine 2000 (Invitrogen, Carlsbad, CA, USA) for 48 h. To confirm that AMPK activation is required for the expression of PGC-1α and MnSOD, HUVECs were treated by 10 µmol/l GSK621 as previous described (18,19).…”
Section: Methodsmentioning
confidence: 99%
“…Cells were incubated at 37˚C in a humidified atmosphere of 5% CO 2 and 95% air and grown to 70 to 80% confluence. For the experiments, the HUVECs were treated with 50, 100 and 200 ng/ml TWEAK respectively based on previous studies (15)(16)(17). As for Fn14 siRNA, for each well of a 6-well plate, cells were transfected with 5 µl siRNA (20 µM) or negative control (Ncontrol group) using Lipofectamine 2000 (Invitrogen, Carlsbad, CA, USA) for 48 h. To confirm that AMPK activation is required for the expression of PGC-1α and MnSOD, HUVECs were treated by 10 µmol/l GSK621 as previous described (18,19).…”
Section: Methodsmentioning
confidence: 99%
“…TWEAK also leads to liver fibrosis progression by directly promoting HSC proliferation. TWEAK, and by enhancing SIRT1 expression and decreasing p53 acetylation, which assumedly inhibits HSC senescence [199, 200]. …”
Section: Mechanisms Of Hsc Activationmentioning
confidence: 99%
“…Moreover, AMPK activation has also been shown to attenuate liver injury and fibrosis in BDL rats through non-canonical NF-κB pathway inhibition and subsequent downregulation of inflammatory cytokines such as Tnf-α , Il-β , Il-21 , and Ccl21 [ 104 ]. However, a recent study suggested that TWEAK-induced SIRT1 upregulation inhibits LX2 cells senescence in parallel with α-SMA increased expression [ 105 ]. Therefore, more studies are required to fully understand the potential roles of SIRT1 in the hepatic fibrogenesis.…”
Section: Acetylation/deacetylation Of Histones In Liver Fibrosismentioning
confidence: 99%